(3GdhGSWIs - (3GdjGRLj , CHh MHjH fGUa Hf YHO Gddg Hf fGUa Hf LfHdGW,J (B1287 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HGdbde bO Yde GdEfSGf eGde jYde hHYO agi ai YQhV GdTYQ CQLhRI cGdRgQ Ch cGdRgQ LYdJgG ai hSW GdeMQGH deJhSW HgPG GdHGH ade Jcf bGHVI Ch HGSWI dPGc eG SejJgG HGdhGSWI s
(3BNQgG (B:s
(3cPGc JMQjQ ENJdGa jUe ai GdVQH hGddg JYGdi CYde s
(3CQLhRIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B350 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B73s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs